Factors and framing effects in support for net zero policies in the United Kingdom - Wouter Poortinga; Wouter Poortinga; Lorraine Whitmarsh; Katharine Steentjes; Emily Gray; Sophie Thompson; Rachel Brisley (Frontiers in Psychology, 2023)
Achieving ambitious carbon reduction targets requires transformative change to society, with behaviour change playing an important role. Climate change mitigation (‘net zero’) policies are needed to accelerate and support such behaviour change. This study examined factors and framing effects in public support for net zero policies in the United Kingdom (UK), making use of a large probability sample (ntotal = 5,665) survey conducted in August 2021. It found that net zero policies are widely supported, with only taxes on red meat and dairy products being supported by less than half of the UK public. Climate worry and perceived fairness were the strongest and most consistent predictors of policy support for net zero policies. The results further suggest that support for net zero policies can be increased by emphasising the co-benefits of the policies, in particular where they are beneficial for health. However, the framing effects were very small. In contrast, public support for net zero policies is lower when potential lifestyle and financial costs are mentioned. This suggests that perceived fairness of the distribution of costs and lifestyle implications of policies are crucial for building and maintaining support for net zero.